The role of digital technology in climate technology innovation - Karam Jo (KDI Journal of Economic Policy, 2023)
In this paper, I empirically estimate the relationship between digital technology and climate technology using the United States Patent and Trademark Office's patent database. I find that innovation in digital technology increases the number of patents for climate technology by 17.3% on average, with digital data-processing technology and machine-learning-related technologies especially playing a key role in this relationship. Designing and implementing detailed policies that take into account the relationship between the two technologies will help us reduce the time required to achieve carbon neutrality and shift to the digital economy.
Keywords: O31; O33; O38; Q48; Q54; Q55; Q58; 330; Digital Technology; Climate Technology; ICT Energy Consumption; Energy Efficiency